Peranan Nilai Tukar Rupiah,Suku Bunga, Indeks Harga Konsumen, dan Harga Minyak Dunia Terhadap Return Saham Pada Industri Manufaktur Di Pasar Saham Indonesia Sebelum dan Sesudah Krisis Ekonomi Global - , Dienni Nuragustin ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this research is to analyze the effect of fundamental macroeconomic factor such as Rupiah exchange rate, interest rate, consumer price index and oil price on manufacture industry stock return in Indonesia before and after economy global crisis caused by sub prime mortgage in 2008. This research also has the purpose of comparing Indonesian manufacturing industry stock return between those terms of period. The data of this research was split into two periods, which represent before sub prime mortgage, 2006 â 2007 data, and after sub prime mortgage, 2009-2010. Stock return data that is used in this research belong to the manufacturing industry stock in Indonesia that has no zero return. Only automotive industry, cement industry, cigarette industry, and food & beverage industry has no zero return in that period. Method that was used in this research is linear regression for paired data test and event study with paired sample t-test. The linear regression for paired data test shows that the only variable that has effect on Indonesian manufacturing industry stock return before sub prime mortgage is rupiah exchange rate with very low significance rate, meanwhile after sub prime mortgage, none of variables mention before that has effect to Indonesian manufacture stock return. Paired sample t-test result show there is difference on Indonesian manufacture industry stock return average before and after sub prime mortgage period, where average return before sub prime mortgage was lower than after.